2014
DOI: 10.1111/bjet.12223
|View full text |Cite
|
Sign up to set email alerts
|

Benefits, barriers and guideline recommendations for the implementation of serious games in education for stakeholders and policymakers

Abstract: Serious games and game-based learning have received increased attention in recent\ud years as an adjunct to teaching and learning material. This has been well echoed in the\ud literature with numerous articles on the use of games and game theory in education.\ud Despite this, no policy for the incorporation of serious games in education exists to date.\ud This review paper draws from the literature to provide guideline recommendations that\ud would help educators and policymakers in making the first step towar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
68
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(85 citation statements)
references
References 62 publications
(111 reference statements)
2
68
0
4
Order By: Relevance
“…Many papers are analysed and summarised as follows, providing useful guidance for this study. Through their systematic review, Tsekleves et al (2014) provide insight into the barriers and benefits of using serious games in education. (Regarding benefits, the authors catalogue: achievement and rewards, interactivity and feedback, motivation and competition, playfulness and problem-based learning, collaborative learning, progression and repetition, as well as realism and immersion.…”
Section: Gamesmentioning
confidence: 99%
See 3 more Smart Citations
“…Many papers are analysed and summarised as follows, providing useful guidance for this study. Through their systematic review, Tsekleves et al (2014) provide insight into the barriers and benefits of using serious games in education. (Regarding benefits, the authors catalogue: achievement and rewards, interactivity and feedback, motivation and competition, playfulness and problem-based learning, collaborative learning, progression and repetition, as well as realism and immersion.…”
Section: Gamesmentioning
confidence: 99%
“…Also, the emergence of a participatory culture in education spurs researchers to get involved with digital games and simulations. Other games mentioned are serious games and their impact on the learning process (Connolly et al, 2012;Bellotti et al, 2013;Backlund & Hendrix, 2013;Tsekleves et al, 2014;Fu et al, 2016). The researchers refer to serious games since they are basically considered as games with educational orientation and not with just entertaining ones.…”
Section: Synthesis Of Previous Reviews/meta-analysesmentioning
confidence: 99%
See 2 more Smart Citations
“…Cooper and Higgins (2015) found that they could not conclude that online instructional videos for undergraduate students improved learning and teaching. Tsekleves, Cosmas, and Aggoun (2016) examined the barriers to the use of serious games in higher education and concluded that it was unclear how games could be incorporated within formal education systems. Furthermore, researchers who undertook a second-order meta-analysis study summarizing 40 years of research concluded that their findings supported arguments by Clark (2001) that technology has little or no effect on student learning (Tamim, Bernard, Borokhovski, Abrami, & Schmid, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%